Alkylated and restored graphene oxide nanoribbon-reinforced isotactic-polypropylene nanocomposites. (November 2016) - Song, Min Yeong; Cho, Se Youn; Kim, Na Rae; Jung, Seok-Heon; Lee, Jin-Kyun; Yun, Young Soo; Jin, Hyoung-Joon
Abstract: Nanostructured carbon materials have outstanding physical properties and high aspect ratios. They have attracted much attention for use as polymer composite reinforcements. In this study, alkylated and reduced graphene oxide nanoribbons (A-rGONRs) were prepared by unzipping multi-walled carbon nanotubes (MWCNTs), followed by a simple alkylation/chemical reduction process using a Dean-Stark trap. A-rGONRs have morphologies with width 30–50 nm and lengths of several micrometers (aspect ratio >100). They are similar to one-dimensional MWCNTs, but with extended interfacial areas and edge functional sites. Approximately 25 wt% of the alkyl chains were chemically introduced onto the surface of A-rGONRs, which gave rise to hydrophobic properties and a surface energy of 23.8 mJ m −2 . A stable A-rGONRs suspension was achieved in xylene even after 24 h. Through a wet process, A-rGONRs were homogeneously dispersed in an isotactic polypropylene (iPP) host. iPP/A-rGONRs nanocomposites showed significant enhancements in thermal and mechanical properties when compared to pure iPP.